Who benefits from ethnic income redistribution? a cross cultural analysis - Grove, D. John; Hoshino, Eiichi (1989)
We know very little about who benefits from the distribution of ethnic income in different parts of the world. Although neoclassical and Marxian theories have come to opposite conclusions concerning who will gain from ethnic income changes, comparativists have largely ignored the question. This cross-cultural study examines the relative gains and losses among 10 pair-wise comparisons in five multiethnic countries. The results show some encouraging signs of interethnic equalization for 7 out of the 10 comparisons, but there are some disturbing reversals in the 1980s. In most cases the dispersion of gains within the upwardly mobile groups are skewed in favor of the richest income groups; however, there are cases where the dispersion of gains is relatively even between top and bottom income groups. Upper-income groups also prospered within the downwardly mobile groups. Thus, the evidence does not support either the Marxian contention that group progress is due to workers usurping the economic privileges of the rich, or the neoclassical position that ethnic equalization is inversely related to within group inequalities.